Carbon Literacy Interventions in Business Education: Assessing Students’Attitudes and Performance before and after Training - Shaaban, Safaa; FakhrEldin, Hadia (Journal of Education and Learning Environments, 2025)
As the urgency for addressing climate change intensifies, the integration of carbon literacy into business education emerges as a pivotal strategy for cultivating environmentally conscious business students. This study examines the impact of carbon literacy programs on business students, focusing on how such programs influence their attitudes and behaviors toward sustainability. Employing a mixed-methods approach, the research analyzes pre and post surveys, alongside qualitative focuses groups interviews, to gauge shifts in understanding and personal commitment to carbon reduction practices. The survey applied the scale adapted form included seventeen items, the sample was 180 students in honor degree (Last year in business school). The findings revealed that exposure to carbon literacy not only enhanced knowledge about environmental issues but also fostered a significant transformation in students' attitudes towards sustainability, leading to initiative-taking behavioral changes. Furthermore, this study highlights the potential of carbon literacy education to instill a sense of responsibility and empowerment among future business leaders, equipping them with the skills needed to make informed decisions that prioritize environmental stewardship in their professional endeavors. This study underscores the necessity of integrating carbon literacy into business curricula to better prepare students to tackle the challenges of climate change in their future careers. A key limitation of this study is the persistent challenge of translating positive attitudes into actual behavioral change among young individuals, particularly university students.